2017
DOI: 10.18844/wjet.v9i1.543
|View full text |Cite
|
Sign up to set email alerts
|

The importance of simulation in nursing education

Abstract: Nursing education involves a practice-oriented curriculum in which emphasis is placed on both theoretical knowledge and psychomotor skills. In skill-based education, where learning through practice occupies a central role, it is important to ensure the integration of theoretical knowledge into practice. In this context, simulations represent an innovative teaching method that stimulates a number of senses at the same time among learners. Simulation is a method which can be designed to reflect real-life conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 0 publications
3
52
0
7
Order By: Relevance
“…However, educating nursing students—thereby ensuring the quality and safety of learning and clinical practice—has always been a challenge for governments, health educators, health managers and the students themselves (Padilha et al, ). In this respect, simulation within a learning environment is an effective educational tool that can be used to achieve the aims of a modern and sustainable nursing education (Eyikara & Baykara, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, educating nursing students—thereby ensuring the quality and safety of learning and clinical practice—has always been a challenge for governments, health educators, health managers and the students themselves (Padilha et al, ). In this respect, simulation within a learning environment is an effective educational tool that can be used to achieve the aims of a modern and sustainable nursing education (Eyikara & Baykara, ).…”
Section: Introductionmentioning
confidence: 99%
“…This research indicated that some institutions failed to do some necessary learning activities for achieving high passing grade (Azizi, Hajibagheri & Adib, 2015). Lesson activities in the classroom with learning method in a case study simulation were really important (Eyikara & Baykara (2017) & Sprinks (2013). Reviewing the questions after periodic of exam, conditioning the question in vignette manner and habituating the students to make bullets and not cross-check model in answering the question were also significant results in this study.…”
Section: Discussionmentioning
confidence: 89%
“…Aside from those factors, there are also factors that affecting students in the process of achieving good final competency exam. Those factors are; the quality of the lectures and clinical instructors, management of planning until evaluating the learning program, learning methods used, infrastructure learning available, the use of up dated information technology and the availability of other learning resources (Eyikara & Baykara (2017) & Abdilah (2016). Combining innovative and high fidelity simulations that delivered in learning process and the clinical experience opportunities will increase the results of the exam.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…*Simulation is a technique that can be formulated to mimic real-life situations that furnishes the liberty to operate in environments that closely resemble real settings (Eyikara and Baykara, 2017). It acts out or imitates an actual or probable real life event for varied purposes such as finding its cause or predicting its outcome.…”
Section: Introductionmentioning
confidence: 99%